2022
DOI: 10.3390/met12071187
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Variable-Diameter Structure on Gas–Solid Heat Transfer in Vertical Shaft Cooler

Abstract: In order to improve the heat transfer between high-temperature sinter and cooling gas in a vertical shaft cooler, a new furnace type with variable-diameter structure was proposed, and the influence of variable-diameter structure on gas–solid heat transfer in vertical-shaft cooler was studied by CFD-DEM coupling method in the current work. The results show that variable-diameter structure can increase the quantity of low-temperature sinter as well as the outlet cooling gas temperature, and can improve the unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Based on this, the authors' team proposed a Venturi furnace type [14] from the perspective of optimizing the shape of the vertical cooling furnace cavity and found that this furnace type can improve the gas-solid contact characteristics, strengthen the gas-solid convective heat transfer, and improve the uniformity of the temperature distribution of sinter and cooling air along the width direction at the cost of increasing the pressure drop of cooling gas. Further research has been conducted on the improvement effect of this furnace type on the distribution of sinter and the gas-solid flow inside the furnace [15].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the authors' team proposed a Venturi furnace type [14] from the perspective of optimizing the shape of the vertical cooling furnace cavity and found that this furnace type can improve the gas-solid contact characteristics, strengthen the gas-solid convective heat transfer, and improve the uniformity of the temperature distribution of sinter and cooling air along the width direction at the cost of increasing the pressure drop of cooling gas. Further research has been conducted on the improvement effect of this furnace type on the distribution of sinter and the gas-solid flow inside the furnace [15].…”
Section: Introductionmentioning
confidence: 99%